Evaluation of Fungicides for the Management of Stripe Rust (Puccinia striiformis f.sp. hordei) of Barley - Kanwar, Harsh Raj; Shekhawat, Pradeep Singh; Kumar, Virendra; Nathawat, B D S (Journal of Cereal Research, 2018)
The field experiment was conducted to evaluate the efficacy of different chemical fungicides against stripe rust of barley caused by Puccinia striiformis f.sp. hordei using susceptible cv. RD 2035 for two consecutive rabi seasons (2016-17 & 2017-18) at Rajasthan Agricultural Research Institute, Durgapura, Jaipur. Among the tested fungicides Trifloxystrobin+Tebuconazole @ 0.1% was found best with minimum disease (8.08 PDS) along with highest yield (56.50 q/ha.). It was followed by Tebuconazole @ 0.1% (9.43 PDS), Trifloxystrobin+Tebuconazole@ 0.05 %, (10.35 PDS) and Tebuconazole @ 0.05% (11.68 PDS). The yield performance of Tebuconazole @ 0.1% (42.33 PDS) and Trifloxystrobin+Tebuconazole @ 0.05 % (54.90 q/ha) were at par with Trifloxystrobin +Tebuconazole @ 0.1 (56.59 q/ha). However, highest and equal B:C ratio (2.8) was recorded in Tebuconazole +Trifloxystrobin @ 0.05% and Tebuconazole @ 0.1% followed by Tebuconazole +Trifloxystrobin @ 0.1% (2.7 B:C) Tebuconazole @ 0.05% (2.6 B:C), propiconazole @ 0.1% (2.6 B:C) and propiconazole @ 0.05% (2.3 B:C).Â Doi.org/10.25174/2249-4065/2018/83425